Analysis And Design Of Accounting Information System Of Purchase Of Credit Spare Parts In PT. Sumber Batu - Daniel Pangondian (Syntax Corporation Indonesia, 2020)
This research was conducted at PT. Sumber Batu which is engaged in contracting. Activities carried out by the company, one of which is the purchase of spare parts on credit. The implementation of the accounting system for purchasing spare parts on credit has not yet fully carried out activities in accordance with internal controls. Data collection was carried out using interview and observation techniques. The analysis conducted was a qualitative descriptive analysis by analyzing and designing Flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and Normalization. Based on research that has been done, researchers can draw the conclusion that there is no duplication of functions applied to the procedure for purchasing spare parts on credit, Keywords : Information System Accounting, Credit Purchases, Internal Control Systems